2020
DOI: 10.1177/0967033520905369
|View full text |Cite
|
Sign up to set email alerts
|

Development of sugarcane and trash identification system in sugar production using hyperspectral imaging

Abstract: Classification and differentiation of clean sugarcane from trash (green sugarcane leaf, dry sugarcane leaf, stone, and soil) are important for the sugar payment system at a sugar mill. Currently, the methods used to do this are manual and subjective. Therefore, this study is aimed at accurately differentiating clean sugarcane from trash by using hyperspectral imaging with multivariate analyses. Samples containing sugarcane billets and trash mixed in a ratio of 18:38 were analyzed in this study. The reflectance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…The experimental results demonstrated correlation coefficients of 0.98, 0.93, and 0.91 for the training, validation, and test sets, respectively. Aparatana et al (2020) employed principal component analysis (PCA), PLS-DA, and support vector machine (SVM) to classify and differentiate sugarcane and impurities, including green leaf, dry leaf, stone, and soil, based on their spectral information. The research findings indicated that PCA, PLS-DA, and SVM achieved classification rates of 90%, 92.9%, and 98.2%, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental results demonstrated correlation coefficients of 0.98, 0.93, and 0.91 for the training, validation, and test sets, respectively. Aparatana et al (2020) employed principal component analysis (PCA), PLS-DA, and support vector machine (SVM) to classify and differentiate sugarcane and impurities, including green leaf, dry leaf, stone, and soil, based on their spectral information. The research findings indicated that PCA, PLS-DA, and SVM achieved classification rates of 90%, 92.9%, and 98.2%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…From the perspective of recognition tasks, the aforementioned studies can be categorized into three types: image classification, object detection, and semantic segmentation. Image classificationbased approaches (Momin et al, 2017;Guedes and Pereira, 2019;Shen et al, 2019;Aparatana et al, 2020;Chen et al, 2020;Guedes et al, 2020;Dos Santos et al, 2021; cannot capture pixel-level information for subsequent construction of a mass-pixel fitting model. Object detection can be utilized for real-time classification and localization of crops and impurities (Zhang et al, 2022;Xu et al, 2023;, but they still cannot support subsequent mass estimation based on pixels of detected objects.…”
Section: Introductionmentioning
confidence: 99%
“…Spectroscopic techniques are widely used in the food and agricultural industries for detection and identification owing to them being fast, accurate, and cost-efficient. The spectrum can also be used to identify sugarcane or predict suger content (Aparatana et al, 2020;Maraphum et al, 2020). A portable visible near-infrared (Vis-NIR) spectrometer has been recently developed and was used to analyze sugarcane because it is reproducible, non-destructive, and convenient for field research (Maraphum et al, 2018;Phuphaphud et al, 2020;Phuphaphud et al, 2019;Sanseechan et al, 2018;Taira et al, 2013;Taira et al, 2015).…”
Section: Introductionmentioning
confidence: 99%